1977
DOI: 10.1021/ed054p750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Keller type course in organic chemistry

Abstract: Evaluation of a Keller Type Course in Organic ChemistryA modified Keller course has been developed and used since 1972 to teach organic chemistry to first year undergraduates in the Chemistry Department at Surrey University. The need for innovation in teaching arose initially as a result of service teaching to biochemists. These students did consistently badly and worse then chemists, who followed the same lecture course, in the final examinations. This was due not to the biochemists' lower ability but to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Which is true for students and teachers? "The organic chemistry course continues to be a traumatic experience for a large number of students" (7) or "Undergraduate organic chemistry education is in an excellent state of health" (2). Our own experience during the last ten years1 has shown that regular lectures were less effective than our approach for teaching the basic course in organic chemistry to chemistry majors.…”
mentioning
confidence: 99%
“…Which is true for students and teachers? "The organic chemistry course continues to be a traumatic experience for a large number of students" (7) or "Undergraduate organic chemistry education is in an excellent state of health" (2). Our own experience during the last ten years1 has shown that regular lectures were less effective than our approach for teaching the basic course in organic chemistry to chemistry majors.…”
mentioning
confidence: 99%
“…From these evaluations the overall impression is that most students learn chemistry by the Keller plan at least as well as by traditional methods of instruction. Some reports even conclude increased learning as a result of Keller plan teaching (1,6,(13)(14)(15).…”
mentioning
confidence: 99%